Analyzing the Factors Influencing Delay of Projects in Zone 3 of Iranian Gas Transmission Company - Ali Attafar; Mohammad Eghbali (مدیریت صنعتی, 2013)
Organizations particularly in project structure pay specialattention to the efficient management and make a lot of efforts to achievethis goal by reducing delay in projects. Gas transmission zones are amongthose kinds of organizations whose main activities are considered to be inproject structure. Thus the significance of project management and thepathology of delay that imposes exorbitant costs on organization will bemore noticeable. In the present essay, project pathology and leadingcauses of delay in the projects of zone 3 of Iranian Gas TransmissionCompany have been investigated. In a similar vein, some managers andexperts have been interviewed and a questionnaire has been used to provetheories from T test and to rank the major causes of delay in projects fromFriedman test. Based on finding from this essay, the most effective causeof project delay from the respondents’ point of view is the contractor'sfailure to perform his obligations and the least effective cause tends to bethe external issues. The findings stemming from this essay can be utilizedfor the purpose of project pathology in all the gas transmission zones andsimilar organizations.